ESCAPING ADMINISTRATIVE TRAP: THE MODERATING ROLE OF MINIMUM SERVICE STANDARDS IN THE LOCAL SPENDING-POVERTY RELATIONSHIP - Rahmah, Mutia; Hamdi, Muchlis; Aminah, Sitti; Berliana, Sarni Maniar (Universitas Padjadjaran, 2025)
This paper aims to examine the significance of minimum service standards (MSS) in moderating the influence of local spending on poverty in various Indonesian districts. This study analyzed 2,072 observations from 148 districts in 2011-2024 using moderated regression analysis (MRA) and STATA 17. The study results show that MSS, which strengthens the influence of local spending on poverty, confirms that its interaction with local spending has a greater impact on poverty. MSS, as both a policy instrument and an administrative action, can reinforce the smoothness and success of program achievements while also encouraging the success of public services. When MSS is subjected to incorrect criteria and mismanagement, its potential to enhance success transforms into an administrative trap that results in the failure of public services at the local government level. Future research can increasingly focus on the various dimensions of MSS in public services, examining both its role as a moderator and its role as an independent variable.